Interplanetary shock induced intensification of electron cyclotron harmonic waves in the Earth’s inner magnetosphere - Xie, Yi; Liu, Nigang; Su, Zhenpeng; Yi, Siyang; He, Zhaoguo; Yu, Jiang; Li, Kun; Chen, Zuzheng; Cui, Jun (Frontiers in Physics, 2024)
Electron cyclotron harmonic (ECH) waves are electrostatic emissions frequently observed in the Earth's magnetosphere. By precipitating magnetospheric hot electrons into the ionosphere, ECH waves play a critical role in the formation of diffuse aurora. Previous research has extensively investigated the strong dependence of ECH waves on the geomagnetic activities. In this study, we present the first report of the prompt response of ECH waves to an interplanetary shock on the basis of WIND and Van Allen Probes observations. Our observations and analyses demonstrate that the interplanetary shock compression can increase >0.1 keV hot electron fluxes in the dayside inner magnetosphere, consequently leading to the prompt intensification of ECH waves by promoting the wave instability. These findings expand our comprehension of the impacts of solar wind disturbances on magnetospheric plasma waves and offer fresh insights into solar wind-magnetosphere-ionosphere coupling.